Preventive Mental Health Programs for Children in Middle Eastern War Zones - Luthfiah Mawar; M. Agung Rahmadi; Annisa Ardianti Br Tarigan; Kiki Asnanti; Siti Nurfaiza; Helsa Nasution; Nurzahara Sihombing; Rasil Hakim Hasibuan (Pusat Riset dan Inovasi Nasional, 2025)
This meta-review presents a comprehensive analysis of the effectiveness of preventive mental health programs targeting children growing up in Middle Eastern conflict zones, systematically examining 47 studies (N=12,487 children) published between 2000 and 2024. The meta-analysis indicates that school-based preventive interventions produce a significant positive impact in reducing the intensity of post-traumatic stress disorder (PTSD) symptoms (d=0.72, 95% CI [0.65, 0.79]), anxiety (d=0.68, 95% CI [0.61, 0.75]), and depression (d=0.64, 95% CI [0.57, 0.71]). Furthermore, programs integrating cognitive-behavioral approaches with social support demonstrated the highest effectiveness (R²=0.83, p<0.001), with recovery rates among children reaching 73.4% compared to control groups. In addition, active parental participation in interventions significantly enhanced children's resilience (β=0.56, p<0.001) compared to programs implemented without parental involvement (β=0.34, p<0.05). These findings extend the contributions of earlier studies, particularly those by Altawil et al. (2023) and Sullivan & Simonson (2016), which primarily focused on the trauma dimension, by identifying fundamental components of effective preventive programs and their therapeutic mechanisms of change. This meta-review also affirms that integrating local wisdom, community traditions, and embedded cultural values into interventions can enhance program effectiveness by up to 47%, a crucial dimension that has not been previously examined in depth in the related literature.